The impact of earnings management on the value of companies: The role of ownership structure - Adam Adamczyk; Sławomir Franek (Journal of Banking and Financial Economics (JBFE), 2022)
The aim of our paper is to test whether there is a relationship between earnings management and the market value of companies with different ownership structures. Additionally, we examined whether ownership control determines earnings management. Our study was conducted on 632 non-financial companies listed on the Warsaw Stock Exchange between 2013 and 2020. We have assessed panel data models showing that there is no relationship between earnings management and company value. However, there is a negative and statistically significant relationship for companies without a majority direct investor. We also showed that, despite the different impact of manipulation on company value, there are no statistically significant differences in earnings management between companies with different ownership structures. The originality of our study lies in conducting an analysis of earnings management taking into account the degree of ownership control.
Keywords: G10; G30; M42; 330; earnings management; M-score; market value; corporate finance